Deciphering the Role of Leptospira Surface Protein LigA in Modulating the Host Innate Immune Response - Kumar, Ajay; Varma, Vivek P.; Sridhar, Kavela; Abdullah, Mohd; Vyas, Pallavi; Ashiq Thalappil, Muhammed; Chang, Yung-Fu; Faisal, Syed M. (Frontiers in Immunology, 2021)
Leptospira, a zoonotic pathogen, is known to infect various hosts and can establish persistent infection. This remarkable ability of bacteria is attributed to its potential to modulate the host immune response by exploiting its surface proteins. We have identified and characterized the domain of the variable region of Leptospira immunoglobulin-like protein A (LAV) involved in immune modulation. The 11th domain (A11) of the variable region of Lig A (LAV) induces a strong TLR4 dependent innate response leading to subsequent induction of humoral and cellular immune responses in mice. A11 is also involved in acquiring complement regulator FH and binds to host protease Plasminogen (PLG), thereby mediating functional activity to escape from complement-mediated killing. The deletion of the A11 domain significantly impaired TLR4 signaling and subsequent reduction in the innate and adaptive immune response. It also inhibited the binding of FH and PLG thereby mediating the killing of bacteria. Our study discovered an unprecedented role of LAV as a nuclease capable of degrading Neutrophil Extracellular Traps (NETs). This nuclease activity was primarily mediated by A11. These results highlighted the moonlighting function of Lig A and demonstrated that a single domain of a surface protein is involved in evading a myriad of host innate immune defenses, which might allow the persistence of Leptospira in different hosts for a long term without clearance.